The Application of Multiuser Detection to Spectrally Efficient MIMO or Virtual MIMO SC-FDMA Uplinks in LTE Systems. - Ben Salem, Aymen (Université d'Ottawa / University of Ottawa, 2014)
Single Carrier Frequency Division Multiple Access (SC-FDMA) is a multiple access transmission scheme that has been adopted in the 4th generation 3GPP Long Term Evolution (LTE) of cellular systems. In fact, its relatively low peak-to-average power ratio (PAPR) makes it ideal for the uplink transmission where the transmit power efficiency is of paramount importance. Multiple access among users is made possible by assigning different users to different sets of non-overlapping subcarriers. With the current LTE specifications, if an SC-FDMA system is operating at its full capacity and a new user requests channel access, the system redistributes the subcarriers in such a way that it can accommodate all of the users. Having less subcarriers for transmission, every user has to increase its modulation order (for example from QPSK to 16QAM) in order to keep the same transmission rate. However, increasing the modulation order is not always possible in practice and may introduce considerable complexity to the system. The technique presented in this thesis report describes a new way of adding more users to an SC-FDMA system by assigning the same sets of subcarriers to different users. The main advantage of this technique is that it allows the system to accommodate more users than conventional SC-FDMA and this corresponds to increasing the spectral efficiency without requiring a higher modulation order or using more bandwidth. During this work, special attentions wee paid to the cases where two and three source signals are being transmitted on the same set of subcarriers, which leads respectively to doubling and tripling the spectral efficiency. Simulation results show that by using the proposed technique, it is possible to add more users to any SC-FDMA system without increasing the bandwidth or the modulation order while keeping the same performance in terms of bit error rate (BER) as the conventional SC-FDMA. This is realized by slightly increasing the energy per bit to noise power spectral density ratio (Eb/N0) at the transmitters.
Keywords: SC-FDMA; Single Carrier Frequency Division Multiple Access; SC-FDE; 3GPP Long Term Evolution; Single Carrier Systems; Single Carrier Systems; Single Carrier FDE; Single Carrier FDMA; Localized Subcarrier Mapping; Distributed Subcarrier Mapping; Orthogonal Frequency Division Multiple Access; OFDMA; MIMO SC-FDMA; Spatial Diversity Gain; Spatial Multiplexing Gain; MIMO Channel; SIMO Channel; Space Diversity on Receive Techniques; Selection Combining; Equal-gain Combining; Maximal-ratio Combining; MRC; Channel Equalization; Zero-forcing Equalization; Minimum Mean-square Error Equalization; ZF; MMSE; SC-FDMA with Multiuser Detection; Spectrally Efficient SC-FDMA with Multiuser Detection; Link Level Simulation; V-blast